Health Coaching terhadap Perilaku dan Efikasi Diri Ibu dalam Pencegahan Stunting - Kansia Anastasia Terok; Yayat Suryati; Dewi Umu Kulsum; Ida Maryati; Fauziah Rudhiati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of health coaching on the behavior and self-efficacy of mothers in preventing stunting: the research method, Quasi-Experimental with pre-test and post-test with a control group design. The statistical results obtained differences in behavior and efficacy before and after treatment in the two groups with p-value <0.05. The difference in the mean post-test behavior with health coaching is 85.55 and with the module 76.88. The mean difference in post-test self-efficacy with health coaching is 41.13 and module 23.88. In conclusion, there is an effect of health coaching and modules on mother's behavior and self-efficacy Keywords: Self-Efficacy, Health Coaching, Preventive Behavior, Stunting